Transisi Guru Ke Pensiun: Mengarungi Perubahan dalam Adaptasi Pasca-Karir - Mario Mario; Musrayani Usman (Universitas Katolik Widya Karya Malang, 2023)
Retirement is an important event that marks the change from adult life to old life. One of the things that need to be prepared in facing retirement is to reduce the workload as retirement approaches. The sociological transition theory developed by William Bridges, known as the